2000
DOI: 10.1093/jnci/92.23.1926
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress and AP-1 Activity in Tamoxifen-Resistant Breast Tumors In Vivo

Abstract: Our results suggest that the conversion of breast tumors to a tamoxifen-resistant phenotype is associated with oxidative stress and the subsequent antioxidant response and with increased phosphorylated JNK and c-Jun levels and AP-1 activity, which together could contribute to tumor growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
104
0
2

Year Published

2002
2002
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(117 citation statements)
references
References 38 publications
11
104
0
2
Order By: Relevance
“…As HER2 upregulation is known to activate Ras/Erk signaling (P , 0.0001; Figure 7E), this observation is in agreement with our data, highlighting cooperation between Ras and JNK signaling. The association of a high JNK signature in ER 1 /HER2 2 ("luminal" subtype) breast cancers is also consistent with reports from previous clinical studies and xenograft models of tamoxifen resistance, which have reported a positive association with activated/phosphorylated JNK ( Johnston et al 1999;Schiff et al 2000), although these tumors do not show high expression of the Ras signature ( Figure 7E). While Ras is not an established oncogene in breast cancer, Ras pathway upregulation is recognized to be important for breast cancer growth and tumorigenesis (reviewed by Whyte et al 2009), and our data support a link between Ras and JNK signaling in HER2 1 breast cancers.…”
Section: Uas-pbl-gfp#8supporting
confidence: 90%
“…As HER2 upregulation is known to activate Ras/Erk signaling (P , 0.0001; Figure 7E), this observation is in agreement with our data, highlighting cooperation between Ras and JNK signaling. The association of a high JNK signature in ER 1 /HER2 2 ("luminal" subtype) breast cancers is also consistent with reports from previous clinical studies and xenograft models of tamoxifen resistance, which have reported a positive association with activated/phosphorylated JNK ( Johnston et al 1999;Schiff et al 2000), although these tumors do not show high expression of the Ras signature ( Figure 7E). While Ras is not an established oncogene in breast cancer, Ras pathway upregulation is recognized to be important for breast cancer growth and tumorigenesis (reviewed by Whyte et al 2009), and our data support a link between Ras and JNK signaling in HER2 1 breast cancers.…”
Section: Uas-pbl-gfp#8supporting
confidence: 90%
“…In addition, they found that the conversion to a resistant phenotype was associated with an increase in oxidative stress (as measured by increases in superoxide dismutases and glutathione-S-transferase). It has been known for some years that tamoxifen can induce intracellular oxidative stress, and these data would be consistent with a model where tamoxifen-induced oxidative stress leads to activation of JNK and increased AP-1 activity (Schiff et al 2000, Clarke et al 2001. Such a chain of events could potentiate the agonistic effects of tamoxifen at AP-1 sites (Webb et al 1995).…”
Section: Pi3k Cell Survival Pathwaysupporting
confidence: 58%
“…These findings have been replicated in a panel of 30 primary human breast tumours with acquired tamoxifen resistance, compared with 27 untreated controls (Johnston et al 1999). Similarly, but using a mouse xenograft model, Schiff and colleagues showed that tamoxifen-resistant tumours, compared with oestrogentreated tumours, had increased AP-1 dependent transcription and phosphorylated c-Jun and JNK levels (Schiff et al 2000). In addition, they found that the conversion to a resistant phenotype was associated with an increase in oxidative stress (as measured by increases in superoxide dismutases and glutathione-S-transferase).…”
Section: Pi3k Cell Survival Pathwaymentioning
confidence: 98%
“…Therefore, the analysis of N-terminal phosphorylation of c-Jun at both S63/73 and T91/T93 is essential for associating c-Jun activation to either prosurvival or pro-apoptotic pathways. To date, c-Jun phosphorylation in response to tamoxifen has been analysed only in tamoxifen-resistant MCF-7-derived xenografts and limited to the S63 site (Schiff et al, 2000).…”
Section: Introductionmentioning
confidence: 99%